The productivity of unemployment: emerging forms of work and life in urban South Africa - Dawson, H (2019)
With two-thirds of South Africa’s young people unemployed, mass joblessness is widely regarded as the country’s most pressing socio- economic crisis. This thesis examines young men’s everyday experiences of unemployment in South Africa. It challenges the dominant understanding of unemployment as a condition characterised by an absence – of income, something to do, or a place in society. Instead, this thesis offers an account of unemployment as an agentive and socially productive experience – punctuated by a multitude of actions, choices, and complex relations of inter-dependence. The findings of this thesis also challenge the assumption that unemployment is inevitably the result of a lack of jobs, showing instead that jobs at the bottom-end of the labour market are at times rejected in favor of alternative modes of socioeconomic life. The thesis is based on twelve months of ethnographic research in Zandspruit, an informal settlement on the outskirts of northern Johannesburg. It offers a detailed account of the ways in which young men make a living outside of wage work. It argues that men’s alternative economic practices are not a last resort, as is often presumed, but rather an active attempt to guard themselves against succumbing to precarious and insecure wage employment. The thesis reveals how young men’s social position within the specific socio-spatial location of Zandspruit mediates their economic choices and work-related decisions while also reinforcing local inequalities. Finally, the thesis examines the wider social, existential, and political implications of such shifts in the historically close relationship between wage work and social order. The findings in this thesis confront a dominant discourse that propounds a ‘crisis of masculinity’ caused by unemployment. They do so by showcasing the diversity of ways young men negotiate their social obligations alongside the other demands in their lives. By revealing the ways in which young men refuse wage work and socially, economically and politically navigate unemployment, this thesis contributes to current political and economic debates about (un)employment and inequality in South Africa – and beyond. In so doing, this thesis makes a case for re-thinking the normative centrality of work both in academic scholarship, and in our social policies and political visions of economic redress and emancipation.